Covid-19 Prevention Protocol Implementation in Construction Projects - Rachmat Mulyana; Meuthia Fadila Fachruddin; Erni Rukmana; Wisnu Prayogo (Journal of Educational, Health and Community Psychology, 2021)
Abstract Construction work projects that are currently underway during the pandemic must implement a protocol to prevent the spread of COVID-19. The purpose of this study was to analyze the implementation of the prevention protocol in several construction work projects in North Sumatera. The data research was collected from the Indrapura–Kisaran highway, the Kuala Tanjung–Tebing Tinggi–Parapat highway, and the RIS Maduma–Dairi University Flats using questionnaire and interviews method. This study result is the contractor provides health measures in an effort to prevent the spread of COVID-19 as follows hand washing area (100%), body temperature check (100%), COVID-19 handling post (66.7%), supplementation (33.3%), provision of hand sanitizer (100%), and medical personnel (66.7%). The nutritional content needs of the workers are met to maintain their immunity (66.7%). The contractors, consultants, and project owners of the three construction projects have implemented the prevention protocol in accordance with the minister’s instructions. Keywords: construction, consumption, COVID-19 pandemic, projects, workers.